Vaginal microbiota during the menopausal transition: the role of lactobacilli - Yulia E. Dobrokhotova; Polina A. Shadrova; Vladimir I. Komagorov (IP Berlin A.V., 2021)
Physiological loss of ovarian function during the menopausal transition often leads to the development of unfavorable symptoms associated with vulvovaginal atrophy, recurrent urinary tract infections and dyspareunia. Currently, the scientific community is actively discussing the risks and benefits of prescribing menopausal hormone therapy to relieve the consequences of estrogen deficiency. The study of vaginal microbiota in dynamics made it possible to take a deeper look at the development of genitourinary menopausal syndrome and associate several microorganisms with specific undesirable manifestations. The link between recurrent urinary tract infections during menopause and physiological replacement of microbiota by opportunistic flora with the development of unpleasant symptoms resolves doctors to resort to irrational courses of antibiotic therapy. The review is devoted to the generalization of information on microbiological changes in the vagina during perimenopause, the possibilities of choosing the optimal hormone therapy for the correction of symptoms, the use of new promising methods, including management by modulating the vaginal microbiota.